2013
DOI: 10.1177/1403494813514301
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of socioeconomic differences in adolescents’ environmental tobacco smoke exposure in Finland: 1991–2009

Abstract: Adolescents' ETS exposure remarkably decreased over time, when tobacco control measures were tightened, particularly among children of smoking parents. Socioeconomic differences persisted although diminishing differences were observed between educational groups at age 16-18.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 20 publications
1
10
0
2
Order By: Relevance
“…A study in China reported that 68 percent of children with less than 18 years of age were exposed to second hand smoke at home, with higher frequency in low-educated and low-income families than in those with higher education and income ( 23 ). This finding is in line with a study in Korea ( 17 ), and a study in Finland that showed reduction in frequency of passive smoking among children whose father had low education level was lower than children whose father had high education level ( 24 ).…”
Section: Discussionsupporting
confidence: 92%
“…A study in China reported that 68 percent of children with less than 18 years of age were exposed to second hand smoke at home, with higher frequency in low-educated and low-income families than in those with higher education and income ( 23 ). This finding is in line with a study in Korea ( 17 ), and a study in Finland that showed reduction in frequency of passive smoking among children whose father had low education level was lower than children whose father had high education level ( 24 ).…”
Section: Discussionsupporting
confidence: 92%
“…No comparable data from other studies are available for Germany. However, international studies confirm the observed trend of declining exposure to passive smoke among adolescents (32,33).…”
Section: Discussionmentioning
confidence: 79%
“…This coaddiction in family circles makes it difficult for deciding to break the habit. Persons living in a smoking environment inhale smoke exhaled by a smoker into the ambient air together with the smouldering smoke and are thus exposed to passive (or forced involuntary) smoking [21]. Passive exposure is widespread and affects a large part of the population at home and in the workplace.…”
Section: Discussionmentioning
confidence: 99%